Adoptive transfer of immune subsets prior to MCAO does not exacerbate stroke outcome in splenectomized mice. Issue 1 (2015) - Wang, Jianming; Dotson, Abby L.; Murphy, Stephanie J.; Offner, Halina; Saugstad, Julie A.
No abstract available